Drug transfer into target helminth parasites - Alvarez, Luis Ignacio (2007)
The pharmacokinetics of an anthelmintic drug includes the time course of drug absorption, distribution, metabolism and elimination from the host and determines the concentration of the active drug that reaches the location of the parasite. However, the action of the anthelmintic also depends on the ability of the active drug to reach its specific receptor within the target parasite. Thus, drug entry and accumulation in target helminths are important issues when considering how best to achieve optimal efficacy. Passive drug transfer through the external helminth surface is the predominant entry mechanism for most widely used anthelmintics and is discussed in this article. Despite the structural differences between the external surface of nematodes (the cuticle) and the external surface of cestodes and trematodes (the tegument), the mechanism of drug entrance into both types of helminth depends on the lipophilicity of the anthelmintic and this is the major physicochemical determinant for the drug to reach a therapeutic concentration in the target parasite. Understanding the processes that regulate drug transfer into helminth parasites is an important aspect in improving the control of parasites in human and veterinary medicine.